On leadership with a preface to the paperback edition - Gardner, John W. (The Free Press, 1990)
Leaders today are familiar with the demand that they come forward with a new vision. But it is not a matter of fabricating a new vision out of whole cloth. A vision relevant for us today will build on values deeply embedded in human history and in our own tradition. It is not as though we come to the task unready. Men and women from the beginning of history have groped and struggled for various pieces of the answer. The materials out of which we build the vision will be the moral strivings of the species, today and in the distant past. Most of the ingredients of a vision for this country have been with us for a long time. As the poet wrote, "The light we sought is shining still." That we have failed and fumbled in some of our attempts to achieve our ideals is obvious. But the great ideas still beckon-freedom, equality, justice, the release of human possibilities. The vision is to live up to the best in our past and to reach the goals we have yet to achieve-with respect to our domestic problems and our responsibilities worldwide.